Reliability Assessment for Cross-cultural Measurement Comparability - Nik Rahimah Nik Yacob; Ismail Rejab (Penerbit Universiti Kebangsaan Malaysia, 1992)
The problem with measurement comparability in cross-cultural studies arises when researchers attempt to attribute differences in obtained scores to cultural inluences. It is a common approach among researchers in marketing to use a standardised instrument cross-culturally to ensure comparability. The author suggests the performance of reliability assessments as a basisfor determining the appropriateness of using standardised instruments although the evidence of comparability is inconclusive.